2022
DOI: 10.5114/ceji.2022.124092
|View full text |Cite
|
Sign up to set email alerts
|

β2-microglobulin alters the profiles of inflammatory cytokines and of matrix metalloprotease in macrophages derived from the osteoarthritic synovium

Abstract: Several studies have implicated β 2-microglobulin (B2M) in osteoarthritis (OA) pathology. Of the main constituents of synovial tissue, synovial fibroblasts and macrophages, the latter play a pivotal role in inflammation. Although several studies have investigated the effects of B2M on synovial fibroblasts, few have examined the impact on synovial macrophages. Here, we investigated the effect of B2M on the expression profiles of inflammatory cytokines and matrix metalloproteases (MMPs) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…B2m and Apod genes were upregulated significantly in the Qua and Sol of Ptrf KO mice and enriched in the “Regulation of cytokine production” term. Previous studies have shown that B2m is associated with immune response and could alter the profiles of inflammatory cytokines 39–42 . Apod regulated cytokine production in the inflammatory response and influenced the cytokine/chemokine inflammatory network 43,44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B2m and Apod genes were upregulated significantly in the Qua and Sol of Ptrf KO mice and enriched in the “Regulation of cytokine production” term. Previous studies have shown that B2m is associated with immune response and could alter the profiles of inflammatory cytokines 39–42 . Apod regulated cytokine production in the inflammatory response and influenced the cytokine/chemokine inflammatory network 43,44 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that B2m is associated with immune response and could alter the profiles of inflammatory cytokines. [39][40][41][42] Apod regulated cytokine production in the inflammatory response and influenced the cytokine/chemokine inflammatory network. 43,44 These results suggested the involvement of the immune system and cytokines in muscular dystrophic muscle.…”
Section: Transcriptome Changes Of Skeletal Muscles In Muscular Dystrophymentioning
confidence: 99%
“…Its loss specifically reduces the lipopolysaccharide-induced inflammatory response of rodent alveolar macrophages [50][51][52][53][54] . Specifically in macrophages, β2-microglobulin alters inflammation osteoarthritis 55 , triggers the inflammasome activation in tumorassociated macrophages 56 , and determines the response to immunotherapy in lung adenocarcinoma 57 . Cux1 is involved in the polarization of tumor-associated macrophages by antagonizing NF-κB signaling 58 .…”
Section: Supplementary Table 4)mentioning
confidence: 99%